2013
DOI: 10.1016/j.jval.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the EQ-5D Health-Related Quality-of-Life Instrument in Assessing Low Back Pain

Abstract: The EQ-5D index is less responsive than instruments specific to pain measurement, although it is capable of indicating clinically important changes. The lower responsiveness arises from EQ-5D's more limited gradation of severity and its multidimensionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 77 publications
3
63
0
Order By: Relevance
“…This lack of significance may be due to a skewed distribution of scores in that an association has been demonstrated in other studies [34,35]. All patients reporting burn-related pain on the BPI-SF also reported pain/discomfort on the EQ-5D, although many patients reporting pain/discomfort on the EQ-5D did not report pain on the BPI-SF.…”
Section: Individual-related Factors Painmentioning
confidence: 75%
See 1 more Smart Citation
“…This lack of significance may be due to a skewed distribution of scores in that an association has been demonstrated in other studies [34,35]. All patients reporting burn-related pain on the BPI-SF also reported pain/discomfort on the EQ-5D, although many patients reporting pain/discomfort on the EQ-5D did not report pain on the BPI-SF.…”
Section: Individual-related Factors Painmentioning
confidence: 75%
“…Pain severity and interference with daily life were mainly considered mild to moderate when assessed according to suggested classifications [33][34][35], and with a high correlation between the two scales. An important and novel finding was that patients reporting pain experienced a significantly lower HRQoL which when measured 3 months after burn was independently related to reporting of pain 2-7 years after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from British Columbia, Canada, Marra et al [22] estimated the mean EQ-5D utility for rheumatoid arthritis to be 0.66. Whynes et al [37] estimated the mean utility score to be 0.64 for mild low back pain and 0.49 for moderate back pain for UK patients.…”
Section: Discussionmentioning
confidence: 99%
“…The EQ-5D was used in the study to estimate the health utility score and to calculate the MIDs associated with different conditions. The EQ-5D was found to be sensitive in terms of detecting meaningful differences in various diseases, although not as sensitive as disease-specific questionnaires [37,43,44]. We used data from a crosssectional study to measure health utilities and MIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Trial patients completed the Brief Pain Inventory (BPI) [19], a patient-reported survey instrument that measures the impact of both pain severity as well as the interference of pain on a variety of outcomes. As one of the most commonly used patient-reported instruments in CLBP patients [20], the BPI has been validated for use in this patient population [21] and has been shown to be responsive to pain-relief treatment in several studies of CLBP patients [13,22,23]. The current analyses examine changes in BPI scores as a function of treatment in order to test the efficacy of BTDS for reducing pain-specific impairments in physical, emotional, social, and everyday functioning.…”
Section: Introductionmentioning
confidence: 99%